2020
DOI: 10.1016/j.ijid.2020.06.080
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal oxygen therapy as an option for early COVID-19

Abstract: There is currently no effective antiviral therapy or immune-based treatment for coronavirus disease . The urgent challenge is to prevent the transition of COVID-19 from mild to severe infection. This paper discussed nocturnal oxygen therapy as a new option for people with COVID-19 under home quarantine. It suggested that nocturnal oxygen therapy in the early stages may be helpful in preventing disease progression by inhibiting the rapid replication of the virus and improving the body's antiviral ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
(45 reference statements)
0
14
0
1
Order By: Relevance
“…Our study identified that in cases of COVID-19, LPV/r treatment maintained statistically significantly higher oxygen saturation values compared with those measured for the group with DRV/r therapy, with a difference of almost 1.89%; but the number of cases that developed acute respiratory failure did not differ significantly between the two groups. Shen et al demonstrated that placing a COVID-19 patient in an nocturnal oxygen-rich environment slowed down viral replication, decreased angiotensin-converting enzyme 2 receptor expression at the target cell, improved antiviral immune response via interferons, T and natural killer cells, and prevented disease progression to the severe form (29).…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified that in cases of COVID-19, LPV/r treatment maintained statistically significantly higher oxygen saturation values compared with those measured for the group with DRV/r therapy, with a difference of almost 1.89%; but the number of cases that developed acute respiratory failure did not differ significantly between the two groups. Shen et al demonstrated that placing a COVID-19 patient in an nocturnal oxygen-rich environment slowed down viral replication, decreased angiotensin-converting enzyme 2 receptor expression at the target cell, improved antiviral immune response via interferons, T and natural killer cells, and prevented disease progression to the severe form (29).…”
Section: Discussionmentioning
confidence: 99%
“…No patient at home isolation, but 26% of hospitalized COVID-19 patients of this study were given oxygen therapy. Decreased hypoxiainducible factor 1α (HIF-1α) could hamper SARS-COV-2 viral replication due to early and proper oxygen therapy [38]. Delivery of 100% oxygen under increased atmospheric pressure up to 2.4 atm through hyperbaric oxygen therapy (HBOT) could improve the patients' outcome if administered at the earliest stages of the COVID-19 infection when arterial oxygen concentration has just been noticed reducing [39].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the hyperinflammatory syndrome usually recover, especially if treated with dexamethasone and/or mAb to inflammatory cytokines, and receive supplemental oxygen [ 27 , 28 ]. However, many patients die or develop a chronic multisystem syndrome that involves the respiratory tract and several other extrapulmonary organs [ 7 ].…”
Section: Metabolic Events During Severe Disease and Chronic Sequelaementioning
confidence: 99%
“…The effects are most evident when the diet is deficient in certain nutrients, such as vitamin A. For example, children receiving a vitamin A deficient diet are more susceptible to measles infection [ 34 ] and the same consequence also might apply to Covid-19 infection [ 28 , 34 ]. Dietary effects, such as fiber and fat content, can also impact on susceptibility to some virus infections.…”
Section: Influence Of Nutrition On Outcome Of Infectionmentioning
confidence: 99%